1996
DOI: 10.1172/jci118566
|View full text |Cite
|
Sign up to set email alerts
|

The acidosis of chronic renal failure activates muscle proteolysis in rats by augmenting transcription of genes encoding proteins of the ATP-dependent ubiquitin-proteasome pathway.

Abstract: Chronic renal failure (CRF) is associated with negative nitrogen balance and loss of lean body mass. To identify specific proteolytic pathways activated by CRF, protein degradation was measured in incubated epitrochlearis muscles from CRF and sham-operated, pair-fed rats. CRF stimulated muscle proteolysis, and inhibition of lysosomal and calcium-activated proteases did not eliminate this increase. When ATP production was blocked, proteolysis in CRF muscles fell to the same level as that in control muscles. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
328
3
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(345 citation statements)
references
References 41 publications
10
328
3
4
Order By: Relevance
“…Evidence exists that the additional protein losses we found with high NaCl intake can also be attributed to these NaCl-induced changes in the acid-base system. In rats, ammonium chloride-induced metabolic acidosis has been shown to 1) stimulate the ubiquitin-proteasome system for muscle proteolysis (8,49), and 2) activate branched-chain ketoacid dehydrogenase, leading to excessive oxidation of branched-chain amino acids in skeletal muscle (7,47). In contrast, our test subjects suffered from mild disturbances of acid-base balance within the normal range (69).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists that the additional protein losses we found with high NaCl intake can also be attributed to these NaCl-induced changes in the acid-base system. In rats, ammonium chloride-induced metabolic acidosis has been shown to 1) stimulate the ubiquitin-proteasome system for muscle proteolysis (8,49), and 2) activate branched-chain ketoacid dehydrogenase, leading to excessive oxidation of branched-chain amino acids in skeletal muscle (7,47). In contrast, our test subjects suffered from mild disturbances of acid-base balance within the normal range (69).…”
Section: Discussionmentioning
confidence: 99%
“…In rat muscle with metabolic acidosis, uremia, or insulin deficiency, the Ub-P'some system is activated (16,18,22), which contributes to muscle protein loss (Figure 1, A and B). Interestingly, we found higher levels of atrogin-1/ MAFbx, the E3 enzyme that is closely associated with activation of protein degradation in muscle of rats with uremia as well as insulin deficiency (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…As in uremia or metabolic acidosis, rats with insulin deficiency have suppressed PI3K activity in muscle, lose weight, and exhibit accelerated muscle proteolysis via activation of the Ub-P'some pathway (16,17,18,22,23). For these reasons and because insulin deficiency is more easily created and less expensive compared with models of metabolic acidosis or uremia, we studied how acute insulin deficiency affects apoptotic and Ub-P'some pathways in muscle (16,22). We confirmed that these rats lose weight and develop muscle atrophy; in the gastrocnemius muscle, we found that the cross-sectional area of muscle fibers (Figure 1, A and B) from four acutely diabetic rats (1390.6 Ϯ 109.2 2 ) was significantly less than that of four pair-fed control rats (2227.4 Ϯ 65.3 2 ; P Ͻ 0.001).…”
Section: Accelerated Muscle Atrophy and Abnormal Insulin Signalingmentioning
confidence: 99%
“…Recently, studies have begun to assess its contribution to the morbidity experienced by patients with nondialysis-dependent CKD (2)(3)(4). Acidosis may contribute to loss of muscle mass through abnormal muscle signaling, IGF-1 dysregulation, insulin resistance, and inflammation (5)(6)(7)(8)(9). Animal models have shown that acidosis promotes muscle proteolysis through impaired phosphatidylinositol 3-kinase (PI3K)/Akt signaling in skeletal muscle (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Acidosis may contribute to loss of muscle mass through abnormal muscle signaling, IGF-1 dysregulation, insulin resistance, and inflammation (5)(6)(7)(8)(9). Animal models have shown that acidosis promotes muscle proteolysis through impaired phosphatidylinositol 3-kinase (PI3K)/Akt signaling in skeletal muscle (5,6). Notably, this pathway mediates the anabolic and anticatabolic effects of IGF-1 and insulin (10), implicating acidosis as one cause of the resistance to both hormones seen in uremia (6,8).…”
Section: Introductionmentioning
confidence: 99%